2004
DOI: 10.1007/s00122-004-1653-5
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale heterospecific segregation distortion in Populus revealed by a dense genetic map

Abstract: We report the most complete genetic map to have been constructed for the genus Populus. This map includes 544 markers mapped onto 19 linkage groups, equivalent to the Populus chromosome number, with all markers displaying internally consistent linkage patterns. We estimate the genome length to be between 2,300 and 2,500 cM, based both on the observed number of crossovers in the maternal haplotypes, as well as the total observed map length. Genome coverage was estimated to be greater than 99.9% at 20 cM per mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
154
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(169 citation statements)
references
References 78 publications
15
154
0
Order By: Relevance
“…Initial screening was conducted with both parents and six progeny, and loci that appeared to be segregating in both parents were selected for mapping. SSR amplification and genotyping was performed as described elsewhere (Yin et al, 2004), except loci were analyzed on an ABI3730 automated capillary electrophoresis instrument, and amplification was performed with 10 pmol fluorescein 12-dUTP (Roche Diagnostics, Indianapolis, IN, USA), rather than end-labeled primers.…”
Section: Ssr Analysismentioning
confidence: 99%
“…Initial screening was conducted with both parents and six progeny, and loci that appeared to be segregating in both parents were selected for mapping. SSR amplification and genotyping was performed as described elsewhere (Yin et al, 2004), except loci were analyzed on an ABI3730 automated capillary electrophoresis instrument, and amplification was performed with 10 pmol fluorescein 12-dUTP (Roche Diagnostics, Indianapolis, IN, USA), rather than end-labeled primers.…”
Section: Ssr Analysismentioning
confidence: 99%
“…Genome organization and chromosome structure have been conserved among Populus and Salix species (Berlin et al 2010), and comparisons among Populus and Salix orthologous genes suggest that both genera share this whole-genome duplication event that predated the speciation event (Tuskan et al 2006). Comparative mapping reveals near-complete marker colinearity in pedigrees established from multiple species within Populus and among members of Salix (Cervera et al 2001;Hanley et al 2006;Yin et al 2004aYin et al , 2008Berlin et al 2010) (Table 1). Interestingly, Berlin et al (2010) identified a large region of segregation distortion on linkage group XIX that corresponds to a similar region in chromosome XIX in Populus .…”
Section: Introductionmentioning
confidence: 99%
“…Dioecy in Populus is strongly genetically controlled, and a region of the genome located on chromosome XIX appears to contain a gene (genes) that controls gender determination, though there are noted examples of gender reversion and hermaphroditic plants in most species (Rottenberg et al 2000;Markussen et al 2007;Gaudet et al 2008;Pakull et al 2009Pakull et al , 2011Paolucci et al 2010). The peritelomeric region on chromosome XIX in female Populus trichocarpa genotypes contains approximately 1 Mb of DNA that is not found in male genotypes and appears to have a region of suppressed and/or reduced recombination that extends 3-4 Mb beyond the hemizygous segment in females (Yin et al 2004a). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epistatic interactions between two or more loci (DobzhanskyMuller incompatibilities) or chromosomal differentiation related to divergence may give rise to transmission ratio distortion in crosses between species or subspecies (reviewed in Fishman and Willis, 2001). Severe transmission ratio distortion has been found in progeny of both interspecific crosses (Fishman and Willis, 2001;Myburg et al, 2004;Yin et al, 2004) and intraspecific crosses between diverged populations (Hall and Willis, 2005;Tö rjék et al, 2006). Earlier studies have generally reported a larger transmission ratio distortion in interspecific crosses than in intraspecific crosses (Zamir and Tadmor, 1986;Jenczewski et al, 1997).…”
Section: Introductionmentioning
confidence: 99%